Pengaruh Model Pembelajaran Team Assisted Individualization (TAI) Terhadap Motivasi Belajar PAK Dan Budi Pekerti Siswa Kelas VIII SMP Negeri 4 Tarutung Tahun Pembelajaran 2023/2024 - Mery Lumbantobing; Rusmauli Simbolon; Lince Lauri Ture Simamora; Ronny Simatupang; Maria Widiastuti (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The aim of this research is to determine the positive and significant influence of the Team Assisted Individualization (TAI) learning model on the PAK Learning Motivation and Characteristics of Class VIII Students of SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 academic year. The method used in this research is a quantitative method with inferential descriptive data analysis. The population is all 122 students of class VIII of SMP Negeri 4 Tarutung for the 2023/2024 academic year who are Protestant Christians and a sample of 49 people was determined using random sampling techniques. Data was collected using a closed questionnaire with 45 items, namely 21 questionnaire items for variable Class VIII of SMP Negeri 4 Tarutung for the 2023/2024 Academic Year, proven through the following data analysis: 1) Test analysis requirements: a) positive relationship test obtained by the value rxy = 0.561 > rtable(=0.05,n=49) = 0.281, so it is known that there is a positive relationship between variable significant difference between variable b) Regression coefficient of determination test (r2) = 31.5%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=20, dk denominator=n-2=49-2=47) namely 21.59 > 1.51. Thus Ha is accepted and H0 is rejected.